Albania : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
In the aftermath of adverse supply shocks, and with further measures to promote investment, growth of production and exports is expected to recover. Efforts to remove barriers to investment and ensure a reliable provision of electricity are critical to private-sector-led growth. External sustainability hinges on further improvements in the business climate to expand the production of tradables, and ongoing fiscal consolidation. Although the Albanian government remains committed to the program, serious risks to growth and the execution of the poverty reduction strategy remain.